Extracellular vesicles: mechanisms and prospects in type 2 diabetes and its complications - Liu, Zijian; Yin, Ruiyang; Tian, Jiaxing (Frontiers in Endocrinology, 2025)
Extracellular vesicles (EVs) are small vesicles released by cells into the surrounding environment, carrying biomolecules such as proteins, miRNA, etc., involved in intercellular communication and regulation of biological processes. With the continuous increase in the prevalence of diabetes, research on the relationship between extracellular vesicles and diabetes has attracted widespread attention. In this article, we specifically focus on the metabolic abnormalities related to EVs and diabetes, including obesity, inflammation, insulin resistance, β-cell damage, etc. We aim to explore how extracellular vesicles participate in the occurrence and development of diabetic complications, comprehensively examining the interactions between extracellular vesicles and key aspects of diabetes, forming a comprehensive and profound research framework. This is expected to provide important clues and insights for deepening our understanding of the pathophysiological mechanisms of diabetes.